ChemInform Abstract: Organic Semiconductors Based on Dyes and Color Pigments. Issue 27 (16th June 2016) - Gsaenger, Marcel; Bialas, David; Huang, Lizhen; Stolte, Matthias; Wuerthner, Frank
Abstract: Review: [156 refs.